Penerapan model pembelajaran kooperatif tipe group investigation untuk meningkatkan hasil belajar PPKn pada siswa XI AP1 SMK Negeri 1 Tampaksiring - I Nyoman Kanten (Indonesian Journal of Educational Development, 2020)
The purpose of this study was to improve learning outcomes of PPKn in class XI AP1 students of SMK Negeri 1 Tampaksiring in semester 2 of the 2018/2019 academic year through the application of Group Investigation cooperative learning models. Subjects in the study were students of class XI AP1 of SMK Negeri 1 Tampaksiring in semester 2 of the 2018/2019 academic year totaling 35 people. The object of the research was the PPKn learning outcomes. Student learning outcomes data in PPKn subjects were collected using tests. Data were analyzed using qualitative descriptive techniques. The study was said to be successful if it met the criteria: (1) the average value of the minimum PPKn test was KKM of 77, and (2) the classical completeness was at least 85%. The results of data analysis showed an increase in student learning outcomes in PPKn subjects in class XI AP1 SMK Negeri 1 Tampaksiring after using the application of the GI type cooperative learning model. In cycle I, the average value of daily tests was 75.21 and classical completeness was 88.57%, while in cycle II the average value of daily tests was 80.68 with a classical completeness of 100%. Thus, the application of the Group Investigation type of cooperative learning model could improve student learning outcomes in PPKn learning after two cycles. Tujuan penelitian ini adalah untuk meningkatkan hasil belajar PPKn pada siswa kelas XI AP1 SMK Negeri 1 Tampaksiring semester 2 tahun pelajaran 2018/2019 melalui penerapan model pembelajaran kooperatif tipe Group Investigation. Subjek dalam penelitian adalah siswa kelas XI AP1 SMK Negeri 1 Tampaksiring semester 2 tahun pelajaran 2018/2019 berjumlah 35 orang. Objek penelitian adalah hasil belajar PPKn. Data hasil belajar siswa dalam mata pelajaran PPKn dikumpulkan menggunakan tes. Data dianalisis menggunakan teknik deskriptif kualitatif. Penelitian dikatakan berhasil bila memenuhi kriteria: (1) nilai rata-rata ulangan PPKn minimal sebesar nilai KKM sebesar 77, dan (2) ketuntasan klasikal minimal 85%. Hasil analisis data menunjukkan terjadi peningkatan hasil belajar siswa pada mata pelajaran PPKn di kelas XI AP1 SMK Negeri 1 Tampaksiring setelah menggunakan penerapan model pembelajaran kooperatif tipe Group Investigation. Pada Siklus I, nilai rata-rata ulangan harian mencapai 75,21 dan ketuntasan klasikal 88,57%, sedangkan pada siklus II nilai rata-rata ulangan harian mancapai 80,68 dengan ketuntasan klasikal sebesar 100%. Dengan demikian, penerapan model pembelajaran kooperatif tipe Group Investigation dapat meningkatkan hasil belajar siswa pada pembelajaran PPKn setelah dilakukan dua kali siklus.